Coated metal plate

By controlling the distribution of large-diameter particles in the organic resin coating layer and using specific resin particles, the problems of large-diameter bead metal sheets falling off and deforming during processing were solved, achieving high design and high productivity of the metal sheets and reducing indentation phenomena that cause gloss changes.

CN121358600APending Publication Date: 2026-01-16NIPPON STEEL CORPORATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202480041676.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-03
Filing Date
2024-07-03
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

In the prior art, metal sheets with organic coatings containing large-diameter beads are prone to detachment and deformation during winding and stamping processes, resulting in reduced design and productivity, and changes in gloss leading to indentation.

Method used

By controlling the distribution density and coverage thickness of large-diameter particles in the organic resin coating layer, the particles are ensured to be evenly distributed in the organic resin coating layer. Specific coating conditions are used to prevent particle detachment and deformation. Polyurethane or acrylic resin particles are used as organic resin particles, combined with zinc plating and anti-rust coating layers to improve corrosion resistance and designability.

Benefits of technology

It effectively prevents particle shedding and deformation, improves the design and productivity of metal sheets, reduces indentation caused by changes in gloss, and maintains the corrosion resistance and aesthetics of metal sheets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121358600A_ABST
    Figure CN121358600A_ABST
Patent Text Reader

Abstract

[Problem] To further improve the designability and productivity of a coated metal plate. [Solution] The present invention pertains to a coated metal plate having: a metal plate; an organic resin coating layer on the surface of the metal plate; and organic resin particles dispersed in the organic resin coating layer, the content of the organic resin particles in the organic resin coating layer being 1.0-16.6 vol% per surface of the organic resin coating layer relative to the total solid content volume of the organic resin coating layer, and the content of the organic resin particles in the organic resin coating layer being 1.0-16.6 vol% per surface of the organic resin coating layer when the organic resin coating layer is viewed from above. The organic resin particles are dispersed in the organic resin coating layer at an areal density of 30-120 particles / mm2, and in a cross section obtained by cutting the organic resin coating layer at an arbitrary position in the thickness direction, the relationships represented by formulae (1)-(4) are established.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to a coated metal sheet. BACKGROUND

[0002] In applications such as home electric appliances, building materials, and automobiles, metal sheets having high designability are being used. As an example of such a metal sheet having high designability, for example, a metal sheet having a colored organic coating film, a metal sheet having a surface with high glossiness, and the like can be given.

[0003] In the metal sheet having high designability as described above, in order to maintain the excellent designability thereof, the damage resistance of the surface of the metal sheet having designability becomes important. Therefore, many proposals have been made for the damage resistance of the metal sheet having high designability.

[0004] For example, in Patent Document 1 below, a technology is proposed in which, in a zinc-based plated steel sheet having an organic coating film, by containing beads having a particle size larger than the film thickness of the organic coating film (hereinafter, also referred to as "large particle size beads") in the organic coating film, the scratch resistance of the organic coating film is improved.

[0005] PRIOR ART DOCUMENTS

[0006] PATENT DOCUMENTS

[0007] Patent Document 1: International Publication No. 2014 / 112544 SUMMARY

[0008] PROBLEMS TO BE SOLVED BY THE INVENTION

[0009] However, if the zinc-based plated steel sheet having the organic coating film containing the large particle size beads proposed in the above Patent Document 1 is coiled into a coiled shape, or a prescribed press working process is performed, sometimes the large particle size beads are detached from the organic coating film, and the designability of the organic coating film can be reduced. In addition, the large particle size beads detached from the organic coating film can contaminate various equipment on which the coiling into a coiled shape or the press working is performed, and the process can be hindered. From the above, in the case of handling the organic coating film containing the large particle size beads, sufficient attention is required at the time of the handling, and from the viewpoint of improving the productivity, there is room for further improvement.

[0010] Furthermore, during the winding of the material into rolls or the application of specified stamping processes, even if large-diameter beads do not detach, they may deform due to the winding tension of the roll or the pressure during stamping. When this deformation occurs, the deformed portion of the organic coating becomes relatively flat, resulting in sometimes localized changes in gloss and a reduction in desired design quality. This reduction in design quality due to changes in gloss is also known as a pressure mark. Therefore, there is room for further improvement in organic coatings containing large-diameter beads from the perspective of maintaining design quality.

[0011] Therefore, the present invention was made in view of the above-mentioned problems, and the object of the present invention is to provide a coated metal sheet having an organic resin coating layer containing particles with a particle size greater than the film thickness, and to achieve further improvements in design and productivity.

[0012] Solution for solving the problem

[0013] To address the aforementioned issues, the inventors conducted in-depth research and arrived at the following concept: if the surface of particles with a diameter greater than the average film thickness contained in an organic resin coating layer can be covered with organic resin, it may be possible to prevent particle detachment and deformation. Based on this concept, the inventors conducted detailed research on the coating conditions of coatings containing particles with a diameter greater than the average film thickness. As a result, the inventors discovered that when specific conditions are met regarding the average particle size, the average film thickness of the organic resin coating layer, and the thickness of the organic resin covering the particle surface, it is possible to prevent particles from detaching from the organic resin coating layer and deforming, thereby further improving the design and productivity of coated metal sheets.

[0014] The gist of the present invention, based on this insight, is as follows.

[0015] [1] A coated metal sheet comprising: a metal sheet; an organic resin coating layer on the surface of the metal sheet; and organic resin particles dispersed in the organic resin coating layer, wherein the content of the aforementioned particles in the organic resin coating layer is 1.0 to 16.6% by volume of the total solids of the aforementioned organic resin coating layer per single side, and when viewed from above, the aforementioned organic resin particles are arranged at a density of 30 to 120 particles / mm. 2 The areal density is dispersed in the aforementioned organic resin coating layer. In the cross section obtained by cutting the aforementioned organic resin coating layer at any position along the thickness direction, the following relationships (1) to (4) hold.

[0016] 10≤T≤40…Equation (1)

[0017] 50≤φ≤100…Equation (2)

[0018] 1.50 ≤ φ / T ≤ 10.00 … Equation (3)

[0019] 15.00 ≤ φ / t ≤ 90.00 … Equation (4)

[0020] In the above, in the above Equation (1) to Equation (4),

[0021] T: average film thickness of the organic resin coating layer in the portion where the organic resin particles are not present in the aforementioned section,

[0022] φ: average particle diameter of the organic resin particles,

[0023] t: average film thickness of the portion where the site of the organic resin particles protruding from the position of the surface of the organic resin coating layer in the aforementioned section is covered with the organic resin coating layer, that is, average film thickness of the particle-covered portion,

[0024] The aforementioned T, the aforementioned φ, and the aforementioned t are in units of μm.

[0025] [2] The coated metal sheet according to [1], wherein the organic resin coating layer is present on both surfaces of the metal sheet, and the organic resin particles are present only in the organic resin coating layer present on one surface of the metal sheet, and the following relationships indicated by Equation (5) and Equation (6) are satisfied with respect to the two organic resin coating layers present on both surfaces of the metal sheet.

[0026] 3 ≤ GA ≤ 30 … Equation (5)

[0027] 0.7 ≤ GA / GB ≤ 1.3 … Equation (6)

[0028] In the above, in the above Equation (5) and Equation (6),

[0029] GA: 60-degree specular glossiness G (60°) of the surface of the organic resin coating layer containing the organic resin particles, as defined in JIS Z 8741: 1997, S

[0030] GB: 60-degree specular glossiness G (60°) of the surface of the organic resin coating layer not containing the organic resin particles, as defined in JIS Z 8741: 1997. S

[0031] [3] The coated metal sheet according to [1] or [2], wherein the aforementioned T and the aforementioned t satisfy the relationship indicated by the following Equation (7).

[0032] 5.0 ≤ T / t ≤ 60.0 … Equation (7)​​

[0033] [4] The coated metal sheet according to [1] or [2], wherein the binder resin contained in the aforementioned organic resin coating layer and the aforementioned organic resin particles satisfy the following relationships shown in Formulas (8) to (10).

[0034] EA≤ EB... Formula (8)

[0035] 60 ≤ EA ≤ 150... Formula (9)

[0036] 60 ≤ EB ≤ 250... Formula (10)

[0037] Herein, in the aforementioned Formulas (8) to (10),

[0038] EA: compressive elastic modulus at 25°C of the binder resin contained in the aforementioned organic resin coating layer,

[0039] EB: compressive elastic modulus at 25°C of the aforementioned organic resin particles,

[0040] The units of the aforementioned EA and the aforementioned EB are MPa.

[0041] [5] The coated metal sheet according to [1] or [2], wherein the aforementioned organic resin particles are resin particles made of a polyurethane-based resin, and the glass transition temperature Tg of the aforementioned polyurethane-based resin is in the range of -40 to 40°C.

[0042] [6] The coated metal sheet according to [1] or [2], wherein the aforementioned organic resin particles are resin particles made of an acrylic-based resin, and the glass transition temperature Tg of the aforementioned acrylic-based resin is in the range of 40 to 160°C.

[0043] [7] The coated metal sheet according to [6], wherein, in a cross section obtained by cutting the aforementioned organic resin coating layer at an arbitrary position in the thickness direction, the cross-sectional shape of at least a portion of the aforementioned resin particles made of the acrylic-based resin is a substantially elliptical shape, the short axis direction of the aforementioned substantially elliptical shape is substantially parallel to the thickness direction of the aforementioned organic resin coating layer, and the long axis direction of the aforementioned substantially elliptical shape is substantially parallel to a direction orthogonal to the aforementioned thickness direction, and the average length Mφ of the short axis of the aforementioned substantially elliptical shape and the aforementioned T satisfy the following relationship shown in Formula (11).

[0044] 1.5 ≤ Mφ / T ≤ 80.0... Formula (11)

[0045] Herein, the unit of the average length Mφ of the aforementioned short axis is μm.

[0046] [8] The coated metal sheet according to [1] or [2], wherein the metal sheet is a zinc-based plated steel sheet in which a zinc-based plating layer containing at least zinc is provided on the surface of a base steel sheet.

[0047] [9] The coated metal sheet according to [8], wherein further, a rust-preventive coating layer containing a rust-preventive pigment and a resin is provided between the organic resin coating layer and the zinc-based plating layer.

[0048]

[10] The coated metal sheet according to [9], wherein the rust-preventive pigment is a pigment containing at least one or more of elements of P, V, Si, and Mg.

[0049]

[11] The coated metal sheet according to [1] or [2], wherein the organic resin coating layer further contains a colorant.

[0050] Effects of the Invention

[0051] As explained above, according to the present application, it is possible to prevent the particles from being peeled off or deformed from the organic resin coating layer, and further improve the designability and productivity of the coated metal sheet. BRIEF DESCRIPTION OF DRAWINGS

[0052] FIG. 1A is a schematic view for explaining an example of the structure of a coated metal sheet according to the present application.

[0053] FIG. 1B is a schematic view for explaining an example of the structure of a coated metal sheet according to the present application.

[0054] FIG. 1C is a schematic view for explaining an example of the structure of a coated metal sheet according to the present application.

[0055] FIG. 1D is a schematic view for explaining an example of the structure of a coated metal sheet according to the present application.

[0056] FIG. 2 is a schematic view for explaining an example of the structure of a coated metal sheet according to the present application.

[0057] FIG. 3 is a schematic view for explaining an example of the structure of a coated metal sheet according to the present application.

[0058] FIG. 4 is a schematic view for explaining an example of the structure of a coated metal sheet according to the present application. DETAILED DESCRIPTION

[0059] Hereinafter, a suitable embodiment of the present application will be described in detail with reference to the accompanying drawings. Note that, in this specification and the drawings, components having substantially identical functions are denoted by like reference numerals, and repeated explanation is omitted.

[0060] (Regarding the coated metal plate)

[0061] <Structure of the coated metal plate>

[0062] Hereinafter, first, the structure of the coated metal plate of the embodiment of the present application will be described with reference to FIG. 1A~FIG. 1D FIG. 1A~FIG. 1D is a schematic view for illustrating an example of the structure of the coated metal plate of the embodiment. Herein, in the present embodiment, the coated metal plate refers to a metal plate having a coating film on a surface. Note that, in the coated metal plate of the present embodiment, coloring agents typified by various dyes and / or pigments can not be contained in the coating film.

[0063] As FIG. 1A schematically shown, the coated metal plate 1 of the present embodiment has a metal plate 10 belonging to a base material and an organic resin coating layer 20 on one surface of the metal plate 10. In addition, the organic resin coating layer 20 of the present embodiment contains organic resin particles 201 in a dispersed state.

[0064] As FIG. 1B schematically shown, in the coated metal plate 1 of the present embodiment, the organic resin coating layer 20 containing the organic resin particles 201 can be provided on one surface of the metal plate 10 belonging to the base material, and the organic resin coating layer 25 not containing the organic resin particles 201 can be provided on the other surface of the metal plate 10.

[0065] As FIG. 1C schematically shown, in the coated metal plate 1 of the present embodiment, the organic resin coating layer 20 containing the organic resin particles 201 can be provided on both surfaces of the metal plate 10 belonging to the base material.

[0066] In addition, in the coated metal plate 1 of the present embodiment, as FIG. 1D schematically shown, a rust-preventive coating layer 30 containing a rust-preventive pigment and a resin can also be provided between the metal plate 10 and the organic resin coating layer 20 as needed.

[0067] Note that, in FIG. 1D , a case where the rust-preventive coating layer 30 is provided in the coated metal plate 1 having the structure shown in FIG. 1A , but a case where the rust-preventive coating layer 30 is not provided in the coated metal plate 1 having the structure shown in FIG. 1B , FIG. 1C ​In the coated metal sheet 1 of the illustrated structure, a rust-preventive coating layer 30 can also be further provided between at least either of the metal sheet 10 and the organic resin coating layer 20 or the metal sheet 10 and the organic resin coating layer 25.

[0068] Next, the details of the coated metal sheet 1 of the illustrated structure will be described. FIG. 1A~FIG. 1D The details of the coated metal sheet 1 of the illustrated structure will be described.

[0069] [About the Metal Sheet 10]

[0070] In the coated metal sheet 1 of the embodiment, as the metal sheet 10 belonging to the base material, various metal sheets can be used. As a blank of such a metal sheet, for example, iron, iron-based alloy, aluminum, aluminum-based alloy, copper, copper-based alloy, titanium, and the like can be cited. In addition, as the metal sheet 10, a plated metal sheet obtained by plating various metal sheets can also be used.

[0071] In addition, in the case where a steel sheet is used as the metal sheet 10, for example, various steel sheets such as Al-killed steel, extremely low carbon steel containing Ti, Nb, and the like, high-strength steel further containing P, Si, Mn, and the like as strengthening elements in the extremely low carbon steel, and the like can be used.

[0072] Among the various metal sheets as described above, as the metal sheet 10 of the embodiment, a zinc-based plated steel sheet obtained by providing a zinc-based plated layer containing at least zinc on the surface of a steel sheet as a base material is preferably used. As the zinc-based plated steel sheet, for example, a zinc-plated steel sheet, a zinc-nickel-plated steel sheet, a zinc-iron-plated steel sheet, a zinc-chromium-plated steel sheet, a zinc-aluminum-plated steel sheet, a zinc-titanium-plated steel sheet, a zinc-magnesium-plated steel sheet, a zinc-manganese-plated steel sheet, a zinc-aluminum-magnesium-plated steel sheet, a zinc-aluminum-magnesium-silicon-plated steel sheet, and the like can be cited. In addition, as the zinc-based plated steel sheet, a zinc-based plated steel sheet containing cobalt, molybdenum, tungsten, nickel, titanium, chromium, aluminum, manganese, iron, magnesium, lead, bismuth, antimony, tin, copper, cadmium, arsenic, and the like as a small amount of foreign metal elements or impurities in the above-described plating, and / or a zinc-based plated steel sheet in which inorganic substances such as silica, alumina, titania, and the like are dispersed can also be used. In addition, as the zinc-based plated steel sheet, a steel sheet having a multilayer plating in which the above-described plating is combined with other kinds of plating (for example, iron plating, iron-phosphorus plating, nickel plating, cobalt plating, and the like) can also be used. The plating method is not particularly limited, and various known plating methods such as electroplating, hot-dip plating, vapor deposition plating, dispersion plating, vacuum plating, and the like can be used.

[0073] In such a zinc-based plating, as the zinc-based plating, a zinc-aluminum-magnesium alloy plating is particularly preferably used, and a zinc-aluminum-magnesium-silicon alloy plating containing Al: 4 to 22 mass%, Mg: 1 to 10 mass%, Si: 0.0001 to 2.0000 mass%, and the balance of Zn and impurities is more preferably used.

[0074] [Al: 4 to 22 mass%]

[0075] By making the content of Al 4 mass% or more, the corrosion resistance of the steel sheet can be further improved. The content of Al is more preferably 5 mass% or more. On the other hand, by making the content of Al 22 mass% or less, saturation of the corrosion resistance improving effect as described above can be suppressed, and the corrosion resistance of the steel sheet can be further improved. The content of Al is more preferably 16 mass% or less.

[0076] [Mg: 1 to 10 mass%]

[0077] By making the content of Mg 1 mass% or more, the corrosion resistance of the steel sheet can be further improved. The content of Mg is more preferably 2 mass% or more. On the other hand, in a plating bath for forming a plated layer, by adjusting the content of Mg in the zinc-based plated layer after production to a Mg concentration of 10 mass% or less, the dross generation in the plating bath can be stabilized, and the plated steel sheet can be stably produced. In the plating bath for forming a zinc-based plated layer, it is more preferable to adjust the content of Mg in the zinc-based plated layer after production to a Mg concentration of 5 mass% or less.

[0078] [Si: 0.0001 to 2.0000 mass%]

[0079] By making the content of Si 0.0001 mass% or more, the adhesion of the zinc-based plated layer (more specifically, the adhesion of the steel sheet as a base material and the zinc-based plated layer) can be further improved. On the other hand, by making the content of Si 2.0000 mass% or less, saturation of the adhesion improving effect of the zinc-based plated layer can be suppressed, and the adhesion of the zinc-based plated layer can be further improved. The content of Si is more preferably 1.6000 mass% or less.

[0080] Further, in the zinc-based plated layer of the present embodiment, 1 mass% or less of elements such as Fe, Sb, and Pb can be contained alone or in combination instead of a part of the balance of Zn.

[0081] As the zinc-based plated steel sheet provided with a zinc-based plated layer having the chemical composition as described above, for example, a hot-dip galvanizing-aluminum-magnesium alloy steel sheet having a Zn-6%Al-3%Mg alloy plated layer, a hot-dip galvanizing-aluminum-magnesium-silicon alloy steel sheet (for example, "SUPER DYM A (registered trademark)" manufactured by Nippon Steel Corporation) having a Zn-11%Al-3%Mg-0.2%Si alloy plated layer, and the like can be given.

[0082] Note that the plated adhesion amount of the zinc-based plated layer as described above is preferably 30 g / m 2 The above (i.e., 15 g / m 2above). By making the attached amount 30 g / m 2 above, so that the corrosion resistance as a zinc-based plated steel sheet can be reliably ensured. The plating attached amount is more preferably 40 g / m 2 above, so that the corrosion resistance as a zinc-based plated steel sheet can be reliably ensured. The plating attached amount is more preferably 40 g / m 2 above (i.e., 300 g / m 2 above). By making the attached amount 600 g / m 2 above, so that the smoothness of the surface of the zinc-based plating layer can be ensured, and further improvement of the corrosion resistance can be achieved. The plating attached amount is more preferably 550 g / m 2 above.

[0083] Note that, in the case where the rust-proof film layer 30 is further provided to the surface of the metal sheet 10 when various plated metal sheets are used as the metal sheet 10, the rust-proof film layer 30 becomes located on the surface of the various plating layers provided to the plated metal sheet.

[0084] Here, the thickness of the metal sheet 10 as described above is not particularly limited, and can be appropriately set in accordance with the mechanical strength (e.g., tensile strength, etc.), workability, etc. required of the coated metal sheet 1 of the present embodiment.

[0085] [About the Organic Resin Film Layer 20]

[0086] Next, the organic resin film layer 20 possessed by the coated metal sheet 1 of the present embodiment will be described. As FIG. 1A~FIG. 1D illustrated in the example, the organic resin film layer 20 of the present embodiment is a film layer in which the organic resin particles 201 exist in a state of being dispersed in the binder resin 203 as a film-forming component. In addition, the organic resin film layer 20 of the present embodiment can contain various additives such as a cross-linking agent, a coloring agent, etc. in addition to the above-described organic resin particles 201 and the binder resin 203.

[0087] In the coated metal sheet 1 of the present embodiment, in the organic resin film layer 20, the organic resin particles 201 are dispersed in the binder resin 203, and the organic resin particles 201 satisfy the conditions described in detail below. Thereby, in the coated metal sheet 1 of the present embodiment, the binder resin 203 achieves the prescribed corrosion resistance and damage resistance, and as the entire coated metal sheet 1 achieves excellent designability that combines a textured appearance and a matte style appearance. Furthermore, in the coated metal sheet 1 of the present embodiment, the generation of dents due to the organic film of the deformed portion becoming relatively flat can be prevented.

[0088] <About the Organic Resin Particles 201>

[0089] In the organic resin coating layer 20 of the present embodiment, the organic resin particles 201 more preferably have a prescribed toughness and ductility. By having the organic resin particles 201 have a prescribed toughness and ductility, it is possible to moderate the impact applied to the organic resin coating layer 20. As a result, in the coated metal sheet 1 of the present embodiment, it is possible to further improve the damage resistance of the organic resin coating layer 20. In addition, by having the organic resin particles 201 have a prescribed toughness and ductility, it is possible to further prevent the generation of dents caused by the organic coating of the deformed portion becoming relatively flat. Furthermore, even if the organic resin coating layer 20 is damaged, it is possible to prevent the damage from reaching the metal sheet 10, and it is possible to maintain the corrosion resistance of the coated metal sheet 1.

[0090] Here, in the organic resin coating layer 20 of the present embodiment, the organic resin particles 201 can use particles formed from various raw materials as long as they have a prescribed toughness and ductility. However, from the viewpoint of having a more excellent toughness and ductility, organic resin particles composed of an organic resin are used in comparison with inorganic particles formed from inorganic compounds typified by silica and ceramics. Note that the organic resin of the present invention refers to a resin including synthetic resins or natural resins, and can contain a small amount of inorganic additives.

[0091] As the organic resin particles 201, for example, resin particles made of an acrylic resin, resin particles made of a polyester-based resin, resin particles made of a polyurethane-based resin, resin particles made of a fluorine-based resin, resin particles made of a silicone resin, resin particles made of a polyolefin-based resin, and the like can be given. Among these, from the viewpoint of being able to more easily achieve the desired toughness and ductility, as the organic resin particles 201, resin particles made of a polyurethane-based resin or resin particles made of an acrylic resin are more preferably used.

[0092] Furthermore, in the case of using resin particles made of a polyurethane-based resin or resin particles made of an acrylic resin as the organic resin particles 201 as described above, it is preferable that the resin constituting these resin particles exhibit a prescribed glass transition temperature Tg.

[0093] More specifically, in the case of using resin particles made of a polyurethane-based resin as the organic resin particles 201, the glass transition temperature Tg of the polyurethane-based resin is preferably in the range of -40°C to 40°C. In addition, in the case of using resin particles made of an acrylic resin as the organic resin particles 201, the glass transition temperature Tg of the acrylic resin is preferably in the range of 40°C to 160°C.

[0094] The constituting resin of the resin particles used as the organic resin particles 201 is made to have a glass transition temperature Tg as described above, whereby the organic resin particles 201 exhibit more preferable toughness and ductility. As a result, even if the particles 201 are deformed by an external force applied to the particles 201, the particles 201 can quickly recover the shape before the impact was applied. Thus, the generation of the indentation caused by the organic coating film of the deformed portion becoming relatively flat can be further prevented.

[0095] In addition, by using the resin particles made of the acrylic resin having the glass transition temperature Tg as described above as the organic resin particles 201, the generation of the indentation as described above can be prevented more inexpensively compared to the case where the resin particles made of the polyurethane-based resin having the glass transition temperature Tg as described above are used.

[0096] However, in the case where the resin particles made of the acrylic resin having the glass transition temperature Tg as described above are used as the organic resin particles 201, the resin particles made of the acrylic resin preferably satisfy a prescribed condition concerning the shape in addition to the glass transition temperature Tg as described above. The condition concerning the shape of the resin particles made of the acrylic resin will be described in detail again below.

[0097] In the case where the resin particles made of the polyurethane-based resin are used as the organic resin particles 201, the glass transition temperature Tg of the polyurethane-based resin is more preferably in the range of -10 to 20°C. In addition, in the case where the resin particles made of the acrylic resin are used as the particles 201, the glass transition temperature Tg of the acrylic resin is more preferably in the range of 60 to 120°C.

[0098] Note that the glass transition temperature Tg can be determined by a method of determining the thermal expansion change of the measurement object by using a thermo mechanical analysis (TMA) to pierce a needle from the surface of the organic resin particles as the measurement object and cause a certain temperature change.

[0099] In the coated metal sheet 1 of the present embodiment, the content of the organic resin particles 201 in the organic resin coating layer 20 is 1.0 to 16.6% by volume per one surface with respect to the total solid content of the organic resin coating layer 20. In the case where the content of the organic resin particles 201 in the organic resin coating layer 20 is less than 1.0% by volume per one surface, the content of the organic resin particles 201 is too small, and the desired design property of combining the textured appearance and the matte style appearance cannot be exhibited. By making the content of the organic resin particles 201 in the organic resin coating layer 20 be 1.0% by volume or more per one surface, the desired design property as the coated metal sheet 1 can be achieved. The content of the organic resin particles 201 in the organic resin coating layer 20 per one surface is preferably 2.2% by volume or more, and more preferably 3.4% by volume or more.

[0100] On the other hand, in the case where the content of the organic resin particles 201 in the organic resin coating layer 20 exceeds 16.6% by volume per one surface, the content of the organic resin particles 201 becomes too large, and as a result, the required damage resistance of the organic resin coating layer 20 cannot be achieved. By making the content of the organic resin particles 201 in the organic resin coating layer 20 be 16.6% by volume or less per one surface, the required damage resistance of the organic resin coating layer 20 can be ensured and the desired design property can be achieved. The content of the organic resin particles 201 in the organic resin coating layer 20 per one surface is preferably 13.3% by volume or less, and more preferably 10.0% by volume or less.

[0101] Here, the method of calculating the content of the organic resin particles 201 in the organic resin coating layer 20 of the coated metal sheet 1 of the present embodiment from the state of the coated metal sheet that has been manufactured will be explained again.

[0102] Note that, as the organic resin particles 201, a plurality of organic resin particles having different average particle diameters can be contained. In addition, the organic resin particles 201 can have a function of, for example, various additives such as a colorant, a rust preventive, and the like, which can be added to the organic resin coating layer 20.

[0103] 《About the Binder Resin 203》

[0104] In addition, the binder resin 203 contained in the organic resin coating layer 20 of the present embodiment as a film-forming component can use any material as long as it functions as a binder of the organic resin particles 201. However, from the viewpoints of ease of manufacturing and cost, and the viewpoints of corrosion resistance and damage resistance, as the binder resin 203, various organic resins are preferably used. As such a binder resin 203, for example, an acrylic resin, a polyester-based resin, a polyurethane-based resin, a fluorine-based resin, and the like can be cited.

[0105] Further, in the organic resin coating layer 20 of the present embodiment, as the binder resin 203, a resin of the same kind as the organic resin particles 201 is more preferably selected. Thereby, the affinity of the organic resin particles 201 to the binder resin 203 is further improved, and the adhesion and barrier properties of the organic resin coating layer 20 can be further improved.

[0106] State of Existence of Organic Resin Particles 201 in Organic Resin Coating Layer 20

[0107] Next, the state of existence of the organic resin particles 201 in the organic resin coating layer 20 will be described in detail with reference to FIG. 2 FIG. 2 is a schematic view for explaining the organic resin particles 201 possessed by the organic resin coating layer of the coated metal sheet of the present embodiment.

[0108] As described above, in the coated metal sheet 1 of the present embodiment, the organic resin particles 201 are dispersed and exist in the organic resin coating layer 20 in a state of being covered with the film-forming component such as the binder resin 203. In discussing the state of existence of the organic resin particles 201, the following, for example, FIG. 2 As schematically shown, attention is paid to a cross section obtained by cutting the organic resin coating layer 20 of the present embodiment at an arbitrary position in the thickness direction.

[0109] In the coated metal sheet 1 of the present embodiment, when the cross section obtained as described above is observed by an electron microscope (more specifically, observed by a field emission scanning electron microscope (FE-SEM)), the following relationships shown by Equations (101) to (104) are respectively established between the average particle diameter of the organic resin particles 201 and the average film thickness of the organic resin coating layer 20.

[0110] 10 ≤ T ≤ 40 … Equation (101)

[0111] 50 ≤ φ ≤ 100 … Equation (102)

[0112] 1.50 ≤ φ / T ≤ 10.00 … Equation (103)

[0113] 15.00 ≤ φ / t ≤ 90.00 … Equation (104)

[0114] ​In the above, in the formulae (101) to (104), T: average film thickness of the organic resin film layer 20 in a portion where the organic resin particles 201 are not present in a cross section, φ: average particle diameter of the organic resin particles 201, t: average film thickness of a portion where the organic resin particles 201 are covered with the organic resin film layer 20 in a portion where the organic resin particles 201 protrude from the surface of the organic resin film layer 20 in the cross section, that is, average film thickness of a "particle-covered portion". Note that the units of T, φ, and t are μm, respectively.

[0115] Further, in investigating the average film thickness T, the average particle diameter φ, and the average film thickness t of the particle-covered portion of the organic resin film layer 20 as described above, in principle, any 100 x 100 μm-sized field of view in the cross section of interest is observed by FE-SEM. Note that in a case where a particle of a large particle diameter that cannot be accommodated in a 100 x 100 μm-sized field of view is observed, in order to accommodate the particle in the field of view, the observation field of view is appropriately increased, and adjustment is made so that the particle diameter, the film thickness of the organic resin film layer, and the film thickness of the particle-covered portion can be measured.

[0116] φ: Average particle diameter of the organic resin particles 201

[0117] In a case where the average particle diameter φ of the organic resin particles 201 is less than 50 μm, the average particle diameter of the organic resin particles 201 is too small, and desired damage resistance cannot be achieved. By making the average particle diameter φ of the organic resin particles 201 50 μm or more, the damage resistance required for the coated metal sheet 1 of the present embodiment can be achieved. The average particle diameter φ of the organic resin particles 201 is preferably 55 μm or more, and more preferably 60 μm or more.

[0118] On the other hand, in a case where the average particle diameter φ of the organic resin particles 201 exceeds 100 μm, the average particle diameter of the organic resin particles 201 is excessively large, and as a result, the organic resin particles 201 easily fall off from the organic resin film layer 20, and desired designability cannot be achieved. By making the average particle diameter φ of the organic resin particles 201 100 μm or less, the organic resin particles 201 can be prevented from falling off from the organic resin film layer 20, and desired designability can be achieved. The average particle diameter φ of the organic resin particles 201 is preferably 90 μm or less, and more preferably 85 μm or less.

[0119] It should be noted that the average particle size φ of the organic resin particles 201 in the cross-section described above is determined by the following steps. First, for each cross-section obtained by cutting the organic resin coating layer 20 at any position, while repeatedly observing and grinding, the measured values ​​for each cross-section obtained by grinding are measured and recorded step by step according to the steps described below, which are used to calculate the average particle size φ of the particles 201, the average film thickness T of the organic resin coating layer 20, and the average film thickness t of the particle-covered portion.

[0120] Here, when determining the average particle size φ of particle 201, the cross-sectional area S of the particle 201 of interest in any field of view in each section is measured step by step as a measured value used to calculate the average particle size φ.

[0121] Next, using the obtained cross-sectional areas S, the corresponding particle size (equivalent circle diameter) can be taken as 2×(S / π). 0.5 The particle size of the organic resin particles 201 existing in a field of view of 100 μm × 100 μm is determined from the observed cross sections. The cross section with the largest determined particle size is selected as one of the cross sections used to determine the average particle size φ of the organic resin particles 201, the average film thickness T of the organic resin coating layer 20, and the average film thickness t of the particle-covered portion.

[0122] In this embodiment, when two or more organic resin particles 201 are observed in a single field of view, the operations of finding the maximum value of the particle size of a particular organic resin particle 201 of interest (e.g., particle A) and finding the maximum value of the particle size of an organic resin particle 201 different from the above (e.g., particle B) are performed independently. The measurements described above are performed on any 20 organic resin particles 201 of interest, and the average of the 20 measurements is used as the average particle size φ of the organic resin particles 201.

[0123] exist FIG. 2 In the example shown, two organic resin particles 201 are present in the field of view. According to the measurement described above, φ1 and φ2 are obtained as the maximum values ​​of the particle size of the organic resin particles 201, respectively. In this case, the above-mentioned values ​​of φ1 and φ2 are used as the measured values ​​of the particle size used to calculate the average particle size φ of the organic resin particles 201.

[0124] Note that, in selecting the cross section from among the plurality of cross sections for determining the average particle diameter φ of the organic resin particles 201, the average film thickness T of the organic resin film layer 20, and the average film thickness t of the particle-covered portion, the following matters need to be noted. That is, in the cross section initially observed, the equivalent circle diameter does not necessarily become the largest. Therefore, slight polishing is performed, and the equivalent circle diameter is repeatedly calculated from the cross-sectional area. The position that becomes the largest is thus searched for.

[0125] The average film thickness T of the organic resin film layer 20 in the portion where the organic resin particles 201 are not present in the cross section

[0126] When the average film thickness T of the organic resin film layer 20 in the portion where the organic resin particles 201 are not present in the cross section is less than 10 μm, the thickness of the organic resin film layer 20 is too thin, and the desired corrosion resistance cannot be achieved. By making the average film thickness T 10 μm or more, the corrosion resistance required for the coated metal sheet 1 of the present embodiment can be achieved. The average film thickness T is preferably 13 μm or more, more preferably more than 15 μm, and further preferably 16 μm or more.

[0127] On the other hand, when the average film thickness T of the organic resin film layer 20 in the portion where the organic resin particles 201 are not present in the cross section exceeds 40 μm, the thickness of the organic resin film layer 20 is too thick, and the adhesion of the organic resin film layer 20 is reduced, and thus is not preferable. By making the average film thickness T 40 μm or less, the adhesion of the organic resin film layer 20 can be ensured and the desired corrosion resistance can be achieved. The average film thickness T is preferably 35 μm or less, and more preferably 30 μm or less.

[0128] Note that the average film thickness T of the organic resin film layer 20 in the portion where the organic resin particles 201 are not present in the cross section described above is determined by the following steps. First, in a field of view in the cross section of interest, the thickness of the organic resin film layer 20 in the portion where the organic resin particles 201 are not present is measured at an arbitrary position. At this time, the thickness of the organic resin film layer 20 in the portion where the organic resin particles 201 are not present can be measured using a length measuring function installed in an FE-SEM or the like. The measurement is performed by changing the field of view five times, and the value obtained by averaging five measurement values is taken as the average film thickness T of the organic resin film layer 20 in the portion where the organic resin particles 201 are not present.

[0129] Here, regarding the cross section used to calculate the average film thickness T described above, the cross section selected for determining the average particle diameter φ of the organic resin particles 201 described above is used.

[0130] In FIG. 2In this case, the thicknesses T1, T2, T3 of the organic resin coating layer 20 in the one field of view of interest were measured at 3 portions where the organic resin particles 201 were not present. In this case, the average value of the thickness of the organic resin coating layer 20 in the one field of view of interest became (1 / 3) x (T1+T2+T3). This observation was performed for any 5 fields of view, and the average values obtained were further averaged with respect to the number of fields of view, whereby the average film thickness T of the portion where the particles 201 were not present was obtained.

[0131] Relationship between the average particle diameter φ of the organic resin particles 201 and the average film thickness T of the organic resin coating layer 20

[0132] In the organic resin coating layer 20 of the present embodiment, the ratio (φ / T) obtained by dividing the average particle diameter φ of the organic resin particles 201 by the average film thickness T is 1.50 or more. In the case where the ratio (φ / T) is less than 1.50, the thickness of the organic resin coating layer 20 is excessively thick compared to the average particle diameter φ of the organic resin particles 201, and as a result, the degree of protrusion of the organic resin particles 201 becomes insufficient, and the desired damage resistance and designability cannot be achieved. By making the ratio (φ / T) 1.50 or more, the required damage resistance of the coated metal sheet 1 can be achieved, and the desired designability can be achieved. The value of the ratio (φ / T) is preferably 1.80 or more, and more preferably 2.00 or more.

[0133] On the other hand, in the case where the value of the ratio (φ / T) exceeds 10.00, the average particle diameter φ of the organic resin particles 201 is excessively large with respect to the average film thickness T, and thus the organic resin particles 201 are difficult to be stably held by the organic resin coating layer 20, and as a result, the organic resin particles 201 become easy to be detached, and the desired designability cannot be achieved. The value of the ratio (φ / T) is preferably 7.00 or less, and more preferably 5.00 or less.

[0134] Relationship between the average particle diameter φ of the organic resin particles 201 and the average film thickness t of the particle-covered portion

[0135] The fact that the ratio (φ / T) becomes 1.50 or more in the above-described equation (103) indicates that there are organic resin particles 201 present in a state of protruding from the position of the surface of the organic resin coating layer 20 where the organic resin particles 201 are not present. Even the organic resin particles 201 in such a state, as shown schematically in FIG. 6, the surface of the organic resin particles 201 is covered with the film-forming components such as the binder resin 203 in the organic resin coating layer 20. FIG. 2 In the following, the relationship between the average particle diameter φ of the organic resin particles 201 and the average film thickness t of the particle-covered portion will be described with reference to FIG. 7. FIG. 2The relationship between the average particle diameter φ of the organic resin particles 201 and the average film thickness of the film-forming component covering the organic resin particles 201 as described above will be described.

[0136] The portion in the cross section mentioned earlier, in which the portion of the organic resin particles 201 that protrudes from the position of the surface of the organic resin film layer 20 in which the organic resin particles 201 are not present is covered with the organic resin film layer 20, will be referred to as a "particle-covered portion". In the example shown in the figure, the substantially semicircular portion located above the line segment L that connects the positions of the surfaces of the organic resin film layer 20 in which the organic resin particles 201 are not present becomes a "particle-covered portion". FIG. 2 In the example shown in the figure, the substantially semicircular portion located above the line segment L that connects the positions of the surfaces of the organic resin film layer 20 in which the organic resin particles 201 are not present becomes a "particle-covered portion".

[0137] In the present embodiment, the average film thickness of the film-forming component covering the surface of the organic resin particles 201 in the particle-covered portion as described above will be denoted by t. The average film thickness t of the particle-covered portion is determined by the following steps.

[0138] First, the positions of the centers of gravity of the organic resin particles 201 present in the field of view of interest are determined. Here, the positions of the centers of gravity can be determined by analyzing the image obtained by microscope observation using a known method. On this basis, a straight line passing through the determined center of gravity and parallel to the surface normal direction of the metal plate 10 is assumedly set. With the thus set straight line as a reference, auxiliary lines in the +45° direction and the -45° direction are assumedly set. The film thickness of the film-forming component present on the thus set auxiliary lines is determined using the length measuring function of the FE-SEM or the like. Thus, from one organic resin particle 201 present in the field of view, the film thicknesses of the film-forming component present on the auxiliary lines in the +45° direction and the -45° direction are determined. FIG. 2 As schematically shown in the figure, two measurement values are obtained.

[0139] As shown in the figure, two organic resin particles 201 are present in one field of view. In this case, measurement values t1, t2 are obtained from the organic resin particle 201 located on the left side in the figure, and measurement values t3, t4 are obtained from the organic resin particle 201 located on the right side in the figure. The average of the thus obtained measurement values (t1+t2+t3+t4) / 4) is taken as the average value of the film thickness of the particle-covered portion in the field of view of interest. FIG. 2 In the case of two organic resin particles 201 present in one field of view, the average of the measurement values obtained from the two organic resin particles 201 is taken as the average value of the film thickness of the particle-covered portion in the field of view of interest. FIG. 2 In the case of two organic resin particles 201 present in one field of view, the average of the measurement values obtained from the two organic resin particles 201 is taken as the average value of the film thickness of the particle-covered portion in the field of view of interest.

[0140] The measurement as described above is performed in any 20 fields of view in the cross section of interest, and the average of the film thicknesses of the particle-covered portions in the respective fields of view is calculated. On this basis, for the plurality of average values obtained, further averaging is performed with respect to the number of fields of view, and the value obtained is taken as the average film thickness t of the particle-covered portion.

[0141] In the organic resin coating layer 20 of the present embodiment, the average film thickness t of the particle-covered portion thus obtained has a value exceeding 0 μm. Further, the greater the average film thickness t of the particle-covered portion, the more effectively the force applied at the time of applying the coiled material to the particle-covered portion, the pressure at the time of press working, and the like can be dispersed, the more effectively the generation of indentations and the like can be suppressed, and the more the designability of the coated metal sheet 1 can be further improved.

[0142] The average film thickness t of the particle-covered portion as described above is preferably 0.6 μm or more, and more preferably 0.7 μm or more. Further, the average film thickness t of the particle-covered portion is preferably 5.0 μm or less, and more preferably 3.0 μm or less.

[0143] Note that, in the case where the straight line passing through the center of gravity of the organic resin particle 201 and parallel to the surface normal direction of the metal sheet 10 itself is taken as the above-mentioned virtual auxiliary line, the film thickness of the film-forming component present on the auxiliary line (for example, in the case of the film-forming component present on the bisector of the angle formed by the two virtual auxiliary lines set to the +45° direction and the -45° direction in FIG. 3 the film thickness of the film-forming component sometimes becomes zero. However, in the present embodiment, the average film thickness t of the particle-covered portion obtained by the above-mentioned method is simply required to exceed 0 μm.

[0144] In the organic resin coating layer 20 of the present embodiment, the ratio (φ / t) defined by the average particle diameter φ of the particle 201 and the average film thickness t of the particle-covered portion thus obtained is 15.00 or more. In the case where the ratio (φ / t) is less than 15.00, the average film thickness t of the particle-covered portion is excessively thick compared to the average particle diameter φ of the organic resin particle 201, and as a result, the degree of protrusion of the organic resin particle 201 becomes insufficient, and the desired damage resistance and designability cannot be achieved. By making the value of the ratio (φ / t) 15.00 or more, the required damage resistance of the coated metal sheet 1 can be achieved, and the desired designability can be achieved. The value of the ratio (φ / t) is preferably 30.00 or more, and more preferably 50.00 or more.

[0145] On the other hand, in the case where the value of the ratio (φ / t) exceeds 90.00, the average particle diameter φ of the organic resin particle 201 is excessively large compared to the average film thickness t, and as a result, the particle 201 is difficult to be stably held by the film-forming component, and the organic resin particle 201 becomes easy to fall off, and the desired designability cannot be achieved. The value of the ratio (φ / t) is preferably 85.00 or less, and more preferably 80.00 or less.

[0146] Relationship between the average film thickness T of the organic resin coating layer 20 and the average film thickness t of the particle-covered portion

[0147] In addition, in the organic resin coating layer 20 of the present embodiment, the average film thickness t of the particle-covered portion obtained as described above and the average film thickness T of the organic resin coating layer 20 in the portion where the organic resin particles 201 are not present in the cross section preferably satisfy the following relationship. More specifically, the ratio (T / t) of the average film thickness T of the organic resin coating layer 20 to the average film thickness t of the particle-covered portion preferably satisfies the relationship shown in the following equation (105).

[0148] 5.0 ≤ T / t ≤ 60.0 … Equation (105)

[0149] By making the ratio (T / t) 5.0 or greater, the organic resin coating layer 20 of the present embodiment can more stably hold the organic resin particles 201, and more excellent damage resistance and designability can be achieved. The ratio (T / t) is more preferably 8.0 or greater.

[0150] On the other hand, by making the ratio (T / t) 60.0 or less, the adhesion of the organic resin coating layer 20 can be ensured and more excellent corrosion resistance can be achieved. The ratio (T / t) is more preferably 50.0 or less.

[0151] Distribution state of the organic resin particles 201 when the organic resin coating layer 20 is viewed from above

[0152] By making the relationships shown in the above equations (101) to (104) hold, in the coated metal sheet 1 of the present embodiment, the particles 201 are covered with the film-forming components of the organic resin coating layer 20, and at the positions where the organic resin particles 201 are present, a distribution state can be achieved that enables recognition of the degree of protrusion of the particles. Thus, in the coated metal sheet 1 of the present embodiment, a characteristic appearance caused by the shape of the organic resin particles 201 is achieved, and high designability is exhibited.

[0153] Here, while referring to FIG. 3 the distribution state of the organic resin particles 201 when the organic resin coating layer 20 is viewed from above is described. FIG. 3 is a schematic view for explaining the organic resin particles possessed by the organic resin coating layer in the coated metal sheet of the present embodiment.

[0154] As FIG. 3 schematically shown, a case where the organic resin coating layer 20 of the present embodiment is viewed from above is focused on. As described above, although the organic resin particles 201 are covered with the film-forming components of the organic resin coating layer 20, when viewed from above, the positions where the organic resin particles 201 are present become a state that can be grasped. In FIG. 3 , the positions of such organic resin particles 201 are indicated by dotted lines.

[0155] In the coated metal plate 1 of this embodiment, as FIG. 3 As exemplified, when viewed from above, the organic resin coating layer 20 has organic resin particles 201 at a density of 30-120 particles / mm. 2 The areal density is dispersed in the organic resin coating layer 20.

[0156] Here, the areal density of the organic resin particles 201 is determined by observing the surface of the organic resin coating layer 20 from above using an optical microscope. More specifically, an arbitrary 1 mm particle is observed using an optical microscope. 2 The number of organic resin particles 201 present in a field of view of varying size is counted. In cases where only a portion of a particle exists in the field of view, rather than the entirety of a particular organic resin particle 201, the number is counted to one decimal place based on the area ratio of the particles present in the field of view, for example, 0.1 to 0.9 particles. Furthermore, if multiple organic resin particles 201 overlap in the thickness direction of the organic resin coating layer 20, the overlapping organic resin particles 201 are counted as one. This counting is performed on any five fields of view, and the average of the five counts is taken as the areal density of the particles 201. Here, when calculating the average value, if the average value includes a decimal value, the decimal value is discarded.

[0157] Here, regarding the shape of the field of view when counting particles, in FIG. 4 The diagram illustrates a rectangular shape, but the shape of the field of view is not particularly limited. The shape of the field of view for counting particles can be, for example, square, polygonal, circular, or elliptical.

[0158] The surface density is less than 30 particles / mm 2 In this case, the number of organic resin particles 201 that contribute to the high designability shown in the coated metal sheet 1 is too small, making it impossible to achieve the designability required by the coated metal sheet 1. Furthermore, in this situation, the protrusion of the organic resin particles 201 becomes insufficient, making it difficult to achieve the damage resistance required by the coated metal sheet 1. By setting the areal density to 30 particles / mm... 2 The above achieves the design requirements and damage resistance of the coated metal sheet 1. The areal density of the organic resin particles 201 is preferably 35 particles / mm². 2 The above is preferred to be 50 pieces / mm. 2 above.

[0159] On the other hand, the areal density of organic resin particles 201 exceeds 120 particles / mm². 2In this case, the probability of a plurality of organic resin particles 201 existing in the thickness direction is increased, and the organic resin particles 201 become easy to fall off, and thus are not preferable. By making the area density 120 pieces / mm 2 Thus, the falling off of the organic resin particles 201 can be suppressed, and the design property and the damage resistance required for the coated metal sheet 1 can be achieved. The area density of the organic resin particles 201 is preferably 110 pieces / mm 2 More preferably, 100 pieces / mm 2 The following.

[0160] Using the area density of the organic resin particles 201, the average particle diameter φ of the organic resin particles 201, and the average film thickness T of the organic resin film layer 20 in which the portion in which the organic resin particles 201 are not present in the cross section, which are determined as described above, the content of the particles 201 in the organic resin film layer 20 in the coated metal sheet 1 of the present embodiment can be determined from the state of the coated metal sheet that has been manufactured. The method thereof will be described below.

[0161] First, assuming that the organic resin particles 201 are spherical, the average volume V of the particles is calculated by the following formula (a) using the average particle diameter φ of the organic resin particles 201. Next, the average volume V of the particles is multiplied by the area density of the organic resin particles 201, and the volume of the organic resin particles 201 per unit area (1 mm 2 ) is calculated. Next, the average film thickness T of the portion in which the organic resin particles 201 are not present is multiplied by 1 mm 2 , and the volume of the organic resin film layer 20 per unit area (1 mm 2 ) is calculated. Thereafter, the volume % can be calculated by the following formula (b).

[0162] V = 4 / 3 π φ 3 … Formula (a)

[0163] Volume % of the organic resin particles 201

[0164] = 100 x area density of the organic resin particles 201 x V ÷ (T x 1 mm 2 ) … Formula (b)

[0165] Note that in the organic resin film layer 20 of the present embodiment, there can be organic resin particles 201 in which a portion of the organic resin particles 201 is not covered with the organic resin film layer 20 and the portion of the organic resin particles 201 is exposed from the organic resin film layer 20. However, the amount of the organic resin particles 201 in which the portion is exposed is preferably as small as possible, and the amount of the organic resin particles 201 in which the portion is exposed is preferably 20 pieces / mm 2 or less in the same area density as described above. More preferably, 0 pieces / mm 2 .

[0166] "Compressive elastic modulus of organic resin particles 201 and binder resin 203"

[0167] Further, in the organic resin coating layer 20 of the present embodiment, the organic resin particles 201 and the binder resin 203 contained in the coating layer more preferably all satisfy the relationships shown in the following Equations (106) to (108).

[0168] EA≤ EB... Equation (106)

[0169] 60 ≤ EA ≤ 150... Equation (107)

[0170] 60 ≤ EB ≤ 250... Equation (108)

[0171] Here, in the above Equations (106) to (108), EA: the compressive elastic modulus at 25°C of the binder resin 203 contained in the organic resin coating layer 20, and EB: the compressive elastic modulus at 25°C of the organic resin particles 201 contained in the organic resin coating layer 20, and the units of EA and EB are MPa.

[0172] By causing the compressive elastic modulus at 25°C shown by each of the organic resin particles 201 and the binder resin 203 to all satisfy the relationships shown in the above Equations (106) to (108), the binder resin 203 is able to more easily follow the deformation of the organic resin particles 201 when the particles are deformed by the application of force from the outside to the organic resin particles 201 (in other words, the binder resin 203 easily deforms more easily along with the deformation of the organic resin particles 201). As a result, the generation of excess voids between the organic resin particles 201 and the binder resin 203 is prevented, and the adhesion and barrier properties of the organic resin coating layer 20 are further improved.

[0173] Here, the compressive elastic modulus at 25°C of the binder resin 203, EA, is more preferably 80 or greater. Further, the compressive elastic modulus at 25°C of the binder resin 203, EA, is more preferably 130 or less. On the other hand, the compressive elastic modulus at 25°C of the organic resin particles 201, EB, is more preferably 90 or greater. Further, the compressive elastic modulus at 25°C of the organic resin particles 201, EB, is more preferably 210 or less.

[0174] Note that the compressive elastic moduli EA, EB of the organic resin particles 201 and the binder resin 203 at 25°C can be determined as follows: by focusing on a cross section obtained by cutting the organic resin coating layer 20 of the present embodiment in the thickness direction, the compressive stress-strain curves of the organic resin particles 201 and the binder resin 203 are each determined. More specifically, according to JIS K 7181:2011, a nanoindenter as an indenter is pressed into the site corresponding to the organic resin particles 201 and the site corresponding to the binder resin 203, respectively, in the cross section of interest, and the load and displacement are measured. At this time, the measurement temperature is set to 25°C. By this measurement, the compressive stress-strain curves can be obtained for the organic resin particles 201 and the binder resin 203, respectively. From the obtained compressive stress-strain curves, the compressive elastic moduli of the organic resin particles 201 and the binder resin 203 can be calculated according to JIS K 7181:2011.

[0175] For the organic resin particles 201 and the binder resin 203, the measurement as described above is performed at 10 sites, respectively, and the average of the obtained plurality of compressive elastic moduli is taken as the compressive elastic modulus EB, EA of the organic resin particles 201 and the binder resin 203 of interest, respectively.

[0176] "Shape of Organic Resin Particles When Using Resin Particles Made of Acrylic Resin"

[0177] In the above, the case where resin particles made of acrylic resin, which preferably satisfy the conditions concerning the shape described below, are used as the organic resin particles 201 is mentioned. Hereinafter, the conditions concerning the preferred shape of the resin particles made of acrylic resin will be described with reference to FIG. 4 to the conditions concerning the preferred shape of the resin particles made of acrylic resin. FIG. 2 is a schematic view for illustrating the organic resin particles possessed by the organic resin coating layer in the coated metal sheet of the present embodiment.

[0178] The resin particles made of acrylic resin, which are an example of the organic resin particles 201 possessed by the organic resin coating layer 20, preferably have a cross-sectional shape of a substantially circular shape as exemplified in FIG. 4 However, at least a part of the resin particles made of acrylic resin can have a cross-sectional shape of a substantially elliptical shape in a cross section obtained by cutting the organic resin coating layer 20 in the thickness direction at an arbitrary position as exemplified in FIG. 4

[0179] In addition, the resin particles made of acrylic resin having a substantially elliptical shape are preferably such that the ratio of the major axis to the minor axis is 1.5 or more and 3 or less, as exemplified in FIG. 4 ​As exemplified, the short axis direction of the substantially elliptical shape is substantially parallel to the thickness direction of the organic resin coating layer 20, and the long axis direction of the substantially elliptical shape is substantially parallel to a direction orthogonal to the thickness direction (in other words, substantially parallel to the surface of the metal sheet 10).

[0180] Further, when the average length of the short axis of the substantially elliptical shape in the resin particles made of the acrylic resin is denoted as Mφ (unit: μm), the average length Mφ and the average film thickness T of the organic resin coating layer 20 in the portion where the organic resin particles 201 are not present preferably satisfy the relationship indicated by the following equation (109).

[0181] 1.5 ≤ Mφ / T ≤ 80.0... Equation (109)

[0182] By the resin particles made of the acrylic resin used as the organic resin particles 201 having the glass transition temperature described above, and even if the cross-sectional shape is a substantially elliptical shape, the cross-sectional shape satisfies the relationship of the above equation (109), so the portion where the resin particles made of the acrylic resin having a substantially elliptical shape are present is not recognized as an indentation. Therefore, even if the resin particles made of the acrylic resin are deformed due to the take-up tension of the web, the pressure at the time of press working, or the like, the design property of the coated metal sheet 1 of the present embodiment can be maintained.

[0183] Here, the average length Mφ of the short axis of the substantially elliptical shape described above can be determined as follows. That is, in the cross section described above for determining the average particle diameter φ of the organic resin particles 201, the average film thickness T of the organic resin coating layer 20, and the average film thickness t of the particle-covered portion, the length of the short axis of the substantially elliptical shape present in an arbitrary field of view is measured. For example, in the field of view, there are FIG. 2~FIG. 4 In the case of the resin particles made of the acrylic resin having an elliptical shape shown in the drawing, the length Mφ1 in the drawing is measured using a length measuring function installed in the FE-SEM or the like. Such measurement is performed on all of the resin particles made of the acrylic resin having a substantially elliptical shape present in the field of view, and the average of the measured values obtained is calculated. Such measurement is performed on 20 fields of view in the cross section, and further, the average of the plurality of average values obtained is calculated with respect to the number of fields of view. The average value thus obtained is the average length Mφ of the short axis of the substantially elliptical shape.

[0184] The ratio (Mφ / T) is preferably 5.0 or more, and more preferably 10.0 or more. In addition, the ratio (Mφ / T) is preferably 70.0 or less, and more preferably 60.0 or less.

[0185] <Concerning Other Ingredients>

[0186] The organic resin coating layer 20 of the present embodiment can contain various additives such as a crosslinking agent, a coloring agent, and the like, in addition to the organic resin particles 201 and the binder resin 203 as described above, as necessary.

[0187] As for the coloring agent described above, there is no particular restriction, and various coloring agents (i.e., various dyes, pigments) known per se can be used according to the color tone required for the organic resin coating layer 20. As such coloring agents, for example, there can be mentioned aluminum pigments, titanium oxide, zinc oxide, zirconium oxide, calcium carbonate, barium sulfate, kaolin clay, carbon black, iron oxide, Hansa yellow, pyrazolone orange, phthalocyanine, azo pigments carbon black, and the like. The content thereof can also be appropriately set, and can be set to about 3 to 60 mass%, for example.

[0188] Further, the organic resin coating layer 20 of the present embodiment can contain, as necessary, additives such as a rust-preventive pigment, a body pigment, a metal powder and / or a glass powder subjected to surface modification, a dispersing agent, a leveling agent, a wax, an aggregate, and the like, a dilution solvent, and the like, within a range that does not impair the effects described above.

[0189] Here, in the case where the organic resin coating layer 20 contains a rust-preventive pigment, the content thereof is preferably set to about 1 to 15 mass%, for example. Further, the rust-preventive pigment to be used can be various rust-preventive pigments known per se.

[0190] The organic resin coating layer 20 of the present embodiment possessed by the coated metal sheet 1 is described in detail below with reference to FIG. 1B

[0191] [About the Organic Resin Coating Layer 25]

[0192] As for the organic resin coating layer 25 that the coated metal sheet 1 of the present embodiment can have, the same constitution as the organic resin coating layer 20 described above is possessed, except that the organic resin particles 201 described above are not contained. That is, the organic resin coating layer 25 contains at least the binder resin 203 as a film-forming component, and can contain various additives. Therefore, detailed description of the organic resin coating layer 25 of the present embodiment is omitted below.

[0193] [About the Rust-Preventive Coating Layer 30]

[0194] Next, the rust-preventive coating layer 30 provided between the metal sheet 10 and the organic resin coating layer 20 in the coated metal sheet 1 of the present embodiment as necessary is briefly described. The rust-preventive coating layer 30 is a coating layer containing a rust-preventive pigment and a resin.

[0195] ​Here, the resin contained in the rust-preventive coating layer 30 functions as a film-forming component, and any raw material can be used. However, from the viewpoints of ease of production and cost, and the viewpoints of corrosion resistance and damage resistance, as the resin, various organic resins are preferably used. As such resins, for example, acrylic resins, polyester resins, polyurethane resins, fluorine resins, and the like can be given.

[0196] In addition, the rust-preventive coating layer 30 of the present embodiment can contain various rust-preventive pigments known in the art as the rust-preventive pigment. However, the rust-preventive coating layer 30 of the present embodiment preferably contains a pigment containing at least one or more of elements of P, V, Si, and Mg as the rust-preventive pigment.

[0197] As the pigment containing at least one or more of elements of P, V, Si, and Mg, for example, zinc phosphate, zinc phosphite, zinc magnesium phosphate, magnesium phosphate, magnesium phosphite, silicon dioxide, calcium ion-exchanged silicon dioxide, zirconium phosphate, aluminum dihydrogen tripolyphosphate, zinc oxide, zinc phosphomolybdate, barium metaborate, strontium chromate, and the like can be given.

[0198] The average film thickness of the rust-preventive coating layer 30 is not particularly limited, and can be set to about 3.0 to 12.0 μm, for example.

[0199] <About the Glossiness of the Coated Metal Sheet 1>

[0200] One of the features of the coated metal sheet 1 of the present embodiment corresponding to high designability is the glossiness showing a matte style appearance. Hereinafter, the glossiness is described in detail.

[0201] In the coated metal sheet 1 of the present embodiment, when the surface of the organic resin coating layer 20 containing the organic resin particles 201 is measured for the 60-degree specular glossiness G S (60°) defined in JIS Z 8741: 1997, the value of the 60-degree specular glossiness G S (60°) is preferably in the range of 3 or more and 30 or less. In the coated metal sheet 1 of the present embodiment, by causing the surface of the organic resin coating layer 20 to show the glossiness in the above range, the coated metal sheet 1 of the present embodiment shows a more excellent matte style appearance (further, more excellent designability). More preferably, the value of the 60-degree specular glossiness G S (60°) is 5 or more. In addition, more preferably, the value of the 60-degree specular glossiness G S (60°) is 25 or less.

[0202] In addition, as FIG. 1A~FIG. 4In the case where the coated metal sheet 1 of the present embodiment has the organic resin coating layer 20 containing the organic resin particles 201 and the organic resin coating layer 25 not containing the organic resin particles 201, as shown, it is preferable that the relationships shown in the following formulas (110) and (111) be satisfied.

[0203] 3 ≤ GA ≤ 30 … Formula (110)

[0204] 0.7 ≤ GA / GB ≤ 1.3 … Formula (111)

[0205] In the above formulas (110) and (111), GA: the 60-degree specular glossiness G S (60°) of the surface of the organic resin coating layer 20 containing the organic resin particles 201, and GB: the 60-degree specular glossiness G S (60°) of the surface of the organic resin coating layer 25 not containing the organic resin particles 201, are defined in JIS Z 8741: 1997. Note that, as for the gloss meter used to measure the 60-degree specular glossiness G S (60°), a gloss meter according to JIS Z 8741: 1997 can be used.

[0206] Even in the case where the coated metal sheet 1 of the present embodiment has the organic resin coating layer 25 not containing the organic resin particles 201, by making the glossiness of the coated metal sheet 1 satisfy both of the above formulas (110) and (111), an excellent matte style appearance can be recognized regardless of which coating layer side the coated metal sheet 1 is recognized from.

[0207] Here, the ratio (GA / GB) is more preferably 0.9 or greater. In addition, the ratio (GA / GB) is more preferably 1.1 or less.

[0208] Note that the 60-degree specular glossiness G S (60°) can be measured using various gloss meters according to JIS Z 8741: 1997.

[0209] The coated metal sheet 1 of the present embodiment has been described in detail above, with reference to ​

[0210] (Regarding the method of manufacturing the coated metal sheet)

[0211] Next, an example of the method of manufacturing the coated metal sheet of the present embodiment will be described.

[0212] First, the metal sheet that becomes the base material is subjected to various pretreatments represented by alkaline degreasing treatment, water washing treatment, pickling treatment, and the like, to produce a clean metal sheet surface. ​

[0213] After that, the metal sheet is coated with various rust-preventive paints known for forming a rust-preventive coating layer as needed, and dried. At this time, the coating of the rust-preventive paint as described above can be performed by a generally known coating method such as roll coating, curtain coating, air spraying, airless spraying, dipping, bar coating, brush coating, or the like. In addition, the heating method for the rust-preventive paint is not particularly limited, and any method such as hot air, near-infrared rays, far-infrared rays, induction heating, a heating method based on a combination thereof, or the like can be employed.

[0214] Next, a coating for forming an organic resin coating layer is coated on the surface of the metal sheet on which the rust-preventive coating layer is formed as needed, and heated and dried, thereby forming the organic resin coating layer. At this time, the coating is prepared by containing the binder resin as described above in a solvent, and containing various additives as needed. In addition, the coating applied to at least one surface of the metal sheet contains the organic resin particles as described above, and the organic resin coating layer 20 is formed.

[0215] At this time, for the coating for forming the organic resin coating layer 20 as described above, the surface tension and the viscosity thereof need to be noted. In more detail, it is important to make the surface tension of the coating be in the range of 28 to 32 mN / m, and to make the viscosity of the coating be in the range of 400 to 700 mPa-s.

[0216] At this time, the surface tension and the viscosity as described above are measured as follows. In addition, the measurement temperature of the surface tension and the viscosity is set to 25°C. In more detail, the surface tension of the coating is measured by the platinum ring method using DY-300 manufactured by Kyowa Interface Science Co., Ltd. In addition, the viscosity of the coating is determined by measuring the relationship between the shear rate and the viscosity of the coating using a rheometer (MCR702e) manufactured by Anton Paar GmbH. At this time, the viscosity of the coating at a shear rate of 1000 s -1 . -1 .

[0217] In addition, it is important that the coating of the prepared coating is performed using a curtain coater. By coating the coating containing the particles using the curtain coater, it is possible to coat the coating without causing the particles to settle or causing coating defects (roping).

[0218] After applying a coating to the surface of a metal sheet (or rust-proof coating), the coating is heated and cured. The heating temperature is set according to the solvent used, preferably within the range of 200-250°C. Furthermore, the heating rate is important when curing the coating. More specifically, it is important to set the heating rate up to the solvent's boiling point within the range of 7-27°C / second. By applying a coating with the aforementioned surface tension and viscosity using a curtain coater and heating it at the aforementioned heating rate, an organic resin coating layer 20 achieving the previously described organic resin particle state can be formed. A heating rate more preferably within the range of 15-25°C / second.

[0219] It should be noted that there are no particular limitations on the heating method for the coating. For example, any method can be used, such as hot air, near-infrared radiation, far-infrared radiation, induction heating, or a combination of these methods.

[0220] The manufacturing method of the coated metal sheet according to this embodiment has been described above.

[0221] Example

[0222] The coated metal sheet of this embodiment will be specifically described below with examples and comparative examples listed. It should be noted that the examples shown below are merely one example of the coated metal sheet of this embodiment, and the coated metal sheet of this embodiment is not limited to the examples described below.

[0223] <1. Preparation of Varnish Coating>

[0224] Toyobo Co., Ltd.'s amorphous polyester resins "Vylon (registered trademark) 500 (Tg 4℃)," "Vylon (registered trademark) 270 (Tg 50℃)," and "Vylon (registered trademark) UR-6100 (Tg -30℃)" were dissolved in an organic solvent (using a mixture of cyclohexanone and Solvesso 150 (trade name) at a mass ratio of 1:1). The mixing ratio of these polyester resins was adjusted.

[0225] Next, to the above solution, a melamine resin "CYMEL (registered trademark) 303" manufactured by Allnex Japan Inc. and a melamine resin "SUPER BECKAMINE (registered trademark)" manufactured by DIC Corporation were added as a curing agent. The melamine resins were added in an amount such that the mass ratio of the solid components of the resins, polyester resin solid component : melamine resin solid component, became 70 : 30. Further, to the mixed solution of the polyester resin and the melamine resin, 0.5 mass% of an acid catalyst "Catalyst 600" manufactured by Allnex Japan Inc. was added. By stirring the mixed solution, a clear paint was obtained. The polyester resin and the melamine resin contained in the clear paint mainly functioned as a binder resin. The compressive elastic modulus of the binder resin was adjusted by adjusting the ratio of the above polyester resin and the ratio of the melamine resin.

[0226] <2. Preparation of the particle-containing paint>

[0227] "Art pearl (registered trademark)", which is a polyurethane resin, manufactured by Kono Industry Co., Ltd., or "MBX", which is an acrylic bead, manufactured by Sekisui Chemical Industry Co., Ltd., were dispersed in the above clear paint, whereby a particle-containing paint was prepared. Further, in some of the levels, carbon black "TOKABLACK #7300" manufactured by Tokai Carbon Co., Ltd. and titanium oxide "R-820" manufactured by Ishihara Sangyo Kaisha, Ltd. were added as a colorant (in Table 1 below, "C.B." is written in the column of "colorant"). Here, the colorant was used in such a manner that the mass ratio (carbon black : titanium oxide) of the above carbon black and titanium oxide became 20 : 80. The amount of the colorant added was set so that the mass ratio (clear paint solid component : colorant) of the solid component of the above clear paint and the colorant became 92 : 8. Further, in some of the levels, only the above titanium oxide was added as a colorant (in Table 1 below, "Ti02" is written in the column of "colorant"). By stirring the mixture, a particle-containing paint was prepared.

[0228] <3. Preparation of the back paint>

[0229] As the back paint, "Flexicoat 100" manufactured by Nippon Paint Industrial Coatings Co., Ltd., which is a polyester / melamine paint, was used. At this time, one colored in beige using a white pigment, a yellow pigment, and the like was used. The glossiness was adjusted by adding silica fine particles as a gloss adjuster to the paint. Further, the dry film thickness was set to 5 μm.

[0230] <4. Preparation of the rust-preventive paint>

[0231] "Vylon (registered trademark) 500 (Tg 4°C)" and "Vylon (registered trademark) 270 (Tg 50°C)" which are amorphous polyester resins manufactured by Toyobo Co., Ltd. were mixed in a mass ratio of 1:1. Next, the polyester resin mixture was dissolved in an organic solvent (Solvesso 150 (trade name) manufactured by Nippon Shokubai Co., Ltd. was used in a mass ratio of 1:1) to produce a primer varnish. To the primer varnish, an isocyanate "CORONATE HX" manufactured by Nippon Shokubai Co., Ltd. was added. The isocyanate was added in a mass ratio of 95:5 of the solid content of the above-mentioned varnish:isocyanate. Further, as a rust-preventive pigment, "K-WHITE #450H" manufactured by TAYCA Co., Ltd., "SHIELDEX C303" manufactured by GRACE Co., Ltd., calcium metavanadate (reagent manufactured by FUJIFILM Wako Pure Chemical Corporation), and magnesium hydroxide (reagent manufactured by Kanto Chemical Co., Ltd.) were used. Each was added in a concentration of 50% by mass in the dried coating film, and the mixture was stirred to produce a rust-preventive paint.

[0232] <5. Preparation of Test Materials>

[0233] Next, as a metal plate to be a base material, various metal plates (all of which are commercially available) were prepared. More specifically, as the metal plate, a Zn-0.2 mass% Al plated steel plate (GI), a Zn-11 mass% Al-3 mass% Mg-0.2 mass% Si plated steel plate (SD), stainless steel 304 (SUS), and aluminum A5052 (Al) were used. The thickness of each metal plate was set to 0.6 mm.

[0234] Here, in order to improve the adhesion between the metal plate and the coating film, a chemical conversion treatment coating film was formed on the surface of the metal plate before the paint was applied. The chemical conversion treatment coating film was formed by applying a chromium-free chemical conversion treatment liquid "CT-E300N" manufactured by Nihon Parkerizing Co., Ltd. under conditions in which the adhesion amount after drying was 100 mg / m 2 , and drying at a metal plate temperature of 60°C.

[0235] On one side of the above metal plate, only the above particle-containing coating was applied, or the above rust-preventive coating and particle-containing coating were applied in two layers, and on the opposite side, a back coating was applied, and heating / baking was performed. In the application of the above coatings, a curtain coater was used. Thus, test materials were produced. Here, a plurality of test materials were produced for each level. The details of the test materials thus produced are shown in Table 1 below. Also, the respective properties of the particle-containing coatings used (surface tension at 25°C, viscosity), and the conditions at the time of heating / baking, are shown in Table 2 below.

[0236] For each of the test materials obtained, the average film thickness T, t, average particle diameter φ, gloss (more specifically, 60-degree specular gloss G S (60°)) GA, GB, particle content, areal density of organic resin particles, compressive elastic modulus EA, EB at 25°C, and the like were measured according to the methods described above. The results obtained are summarized in Table 1 below. Also, for the test materials of the embodiment, the amount of existence of particles partially exposed was confirmed, and as a result, it was confirmed that the amount of existence was less than the upper limit value (20 pieces / mm 2 ) allowed. Note that, for the confirmation, cross-sectional observation was repeatedly performed while observing and grinding the resin-embedded sample, and the number of particles was observed for a cross-sectional area equivalent to 1 mm 2 .

[0237] [Table 1]

[0238]

[0239] [Table 2]

[0240]

[0241] For each of the test materials obtained as described above, evaluation was performed from the viewpoints of texture appearance, process adhesion, indentation, and corrosion resistance. The evaluation methods are described below.

[0242] (Texture appearance)

[0243] Instead of the test material surface, a resin molded product (having a texture appearance, resin used: outer finish material of Canon Inc. multifunctional machine iR ADVC5250F) was used. For the test material and the resin molded product, visual observation from a distance of 30 cm and tactile sensation by hand touch were respectively evaluated, and discrimination with the test material was investigated. The evaluators were any 20 people with visual acuity of 1.0 or more. The proportion of the number of evaluators who could discriminate between the two out of 20 evaluators was calculated as the discriminability, and was used as an evaluation relating to design. The evaluation criteria are described below. The pass level was set to 3 or more.

[0244] <Evaluation criteria>

[0245] Rating 5: Discrimination rate is 0%

[0246] 4: The discriminant rate is greater than 0% but less than 10%.

[0247] 3: The discrimination rate is higher than 10% but lower than 20%.

[0248] 2: The discrimination rate is higher than 20% but lower than 50%.

[0249] 1: The discrimination rate exceeds 50%

[0250] (Processing tightness)

[0251] The cylindrical cup is formed with the test material surface facing outwards. A die with a diameter of φ50mm is used. The shoulder radius (R) of both the die and punch is set to 5mm. The drawing height is set to 50mm, and the blank holder force is set to 1ton. After processing, transparent tape (Cellotape manufactured by Nichiban Co., Ltd. (registered trademark), 24mm wide) is applied to the cup body. Then, the transparent tape is peeled off at a 45° angle relative to the surface normal of the test material. The paint adhesion area on the peeled transparent tape is visually evaluated. Processing tightness is evaluated according to the following criteria, as part of the design considerations. A pass / fail level is set to 3 or higher.

[0252] <Evaluation Criteria>

[0253] Rating 5: No coating peeling

[0254] 4: Coating peel area ratio is less than 5%

[0255] 3: The coating peeling area rate is 5% or more but less than 10%.

[0256] 2: The coating peeling area rate is 10% or more but less than 30%.

[0257] 1: Coating peel area rate is over 30%

[0258] (Indentation)

[0259] Using two test materials of the same level, overlap the surface of one test material with the back of the other, and then apply pressure of 10 MPa. The test temperature is set at 50°C, and the test time is set at 10 minutes. After the test, visually evaluate the appearance of the surface and assess the presence or absence of indentations. Evaluate indentation performance according to the following evaluation criteria as part of the design considerations. A passing level is set at 3 or higher.

[0260] <Evaluation Criteria>

[0261] Score 5: No indentation can be observed whether viewed from the front (the direction of the surface normal of the test material) or from an oblique angle.

[0262] 4: No indentation is observed from the front, but indentation is slightly observed from the oblique.

[0263] 3: Indentation is slightly observed from the front, and indentation is slightly observed from the oblique.

[0264] 2: Indentation is slightly observed from the front, and indentation is clearly observed from the oblique.

[0265] 1: Indentation is clearly observed from both the front and the oblique.

[0266] (Erosion Resistance)

[0267] An X-shaped notch was formed on the surface of the test material using an NT cutter. At this time, the damage reached the metal plate as the base material. Thereafter, a salt spray test (SST) according to JIS Z 2371:2015 was performed for 240 hours. The test material after the test was washed, dried, and the maximum expansion width from the X-shaped notch portion was measured. Of the expansion generated on both sides of the damage portion, the maximum expansion width of one side was measured. A 10-fold magnifying lens was used in the observation. The erosion resistance was evaluated in accordance with the following evaluation criteria. The pass level was set to 3 or more.

[0268] <Evaluation Criteria>

[0269] Score 5: Maximum expansion width less than 2 mm

[0270] 4: Maximum expansion width 2 mm or more and less than 3 mm

[0271] 3: Maximum expansion width 3 mm or more and less than 5 mm

[0272] 2: Maximum expansion width 5 mm or more and less than 7 mm

[0273] 1: Maximum expansion width 7 mm or more

[0274] The results obtained are summarized in Table 3 below.

[0275] [Table 3]

[0276]

[0277] As shown from Table 3 above, the test material corresponding to the examples of the present application showed excellent texture appearance, process adhesion, indentation, and erosion resistance, and on the other hand, at least either one of the texture appearance or the process adhesion of the test material corresponding to the comparative examples of the present application became unqualified.

[0278] Note that in No. 26 and No. 27 in which stainless steel 304 (SUS) or aluminum A5052 (Al) was used as the metal sheet, the metal sheet was broken when the cylindrical cup forming for evaluating the "process adhesion" was performed, and thus the "process adhesion" could not be evaluated. Therefore, in Table 3 above, the column of "process adhesion" of No. 26 and No. 27 is described as "-".

[0279] In addition, the productivity when the particle-containing coating material of No. 1 shown in Table 1 above was applied using a curtain coater and a roll coater commonly used in the production of pre-coated steel sheets was compared. The roll coater used a double roll coater composed of a pickup roll and an applicator roll. The substrate speed was changed at intervals of 10 mpm between 10 mpm and 80 mpm.

[0280] In the case of the curtain coater, a beautiful appearance was obtained in the range of 50 to 80 mpm of the speed of the metal sheet, and as for the performance, a performance equivalent to that of No. 1 shown in Table 1 above was also exhibited. On the other hand, in the case of the roll coater, in the range of 20 to 80 mpm of the running speed, a streak was generated, and on the other hand, in the case of 10 mpm of the running speed, a beautiful appearance was obtained as in the case of coating using the curtain coater. From this result, it can be said that if coating is performed using the curtain coater, the productivity is 5 to 8 times higher than that of the roll coater which is a commonly used coating method.

[0281] The above-described embodiments of the present application have been described in detail with reference to the accompanying drawings, but the present application is not limited to the above examples. It will be apparent to those skilled in the art with ordinary knowledge that various modifications or changes can be conceived within the scope of the technical concept recited in the claims, and it should be understood that such modifications or changes naturally belong to the scope of protection of the present application.

[0282] The embodiments disclosed this time achieve the object of the present application, but the present application is not limited to the embodiments disclosed this time, but can be changed in various ways without departing from the spirit and scope of the present application. That is, the technical features of the above embodiments can be arbitrarily combined so long as the combination does not interfere with each other, and it is understood that the resulting technical features also belong to the scope of the present application.

[0283] In addition, the effects described in the present specification are merely illustrative or exemplary, and are not limited. That is, along with or in place of the effects described above, the technical features of the present application can exhibit other effects apparent for those skilled in the art from the description of the present specification.

[0284] It should be noted that the following configuration also falls within the scope of the present application. [1]

[0286] A coated metal sheet having: a metal sheet; an organic resin coating layer on a surface of the metal sheet; and organic resin particles dispersed in the organic resin coating layer,

[0287] The content of the organic resin particles in the organic resin coating layer is 1.0 to 16.6% by volume per one surface with respect to the total solid content volume of the organic resin coating layer,

[0288] When the organic resin coating layer is viewed from above, the organic resin particles are dispersed in the organic resin coating layer at a surface density of 30 to 120 pieces / mm 2 ,

[0289] In a cross section obtained by cutting the organic resin coating layer in an arbitrary position in the thickness direction, the following relationships shown by Formulas (1) to (4) are satisfied.

[0290] 10 ≤ T ≤ 40 … Formula (1)

[0291] 50 ≤ φ ≤ 100 … Formula (2)

[0292] 1.50 ≤ φ / T ≤ 10.00 … Formula (3)

[0293] 15.00 ≤ φ / t ≤ 90.00 … Formula (4)

[0294] Here, in the above Formulas (1) to (4),

[0295] T: average film thickness of the organic resin coating layer in the portion where the organic resin particles are not present in the cross section,

[0296] φ: average particle diameter of the organic resin particles,

[0297] t: average film thickness of the portion where the portion of the organic resin particles protruding from the position of the surface of the organic resin coating layer in the cross section is covered with the organic resin coating layer, that is, average film thickness of the particle-covered portion,

[0298] The units of the above T, φ, and t are μm. [2]

[0300] The coated metal sheet according to [1], wherein the organic resin coating layer is on both surfaces of the metal sheet, and the organic resin particles are present only in the organic resin coating layer on one surface of the metal sheet,

[0301] With respect to the two aforementioned organic resin coating film layers on the two surfaces of the aforementioned metal sheet, the following relationships shown in Formula (5) and Formula (6) are satisfied.

[0302] 3 ≤ GA ≤ 30 … Formula (5)

[0303] 0.7 ≤ GA / GB ≤ 1.3 … Formula (6)

[0304] Herein, in the aforementioned Formula (5) and Formula (6),

[0305] GA: 60-degree specular glossiness G specified in JIS Z 8741:1997 of the surface of the aforementioned organic resin coating film layer containing the aforementioned organic resin particles S (60°),

[0306] GB: 60-degree specular glossiness G specified in JIS Z 8741:1997 of the surface of the aforementioned organic resin coating film layer not containing the aforementioned organic resin particles S (60°). [3]

[0308] The coated metal sheet according to [1] or [2], wherein the aforementioned T and the aforementioned t satisfy the following relationship shown in Formula (7).

[0309] 5.0 ≤ T / t ≤ 60.0 … Formula (7) [4]

[0311] The coated metal sheet according to any one of [1] to [3], wherein the binder resin contained in the aforementioned organic resin coating film layer and the aforementioned organic resin particles satisfy the following relationships shown in Formula (8) to Formula (10).

[0312] EA ≤ EB … Formula (8)

[0313] 60 ≤ EA ≤ 150 … Formula (9)

[0314] 60 ≤ EB ≤ 250 … Formula (10)

[0315] Herein, in the aforementioned Formula (8) to Formula (10),

[0316] EA: compressive elastic modulus at 25°C of the binder resin contained in the aforementioned organic resin coating film layer,

[0317] EB: compressive elastic modulus at 25°C of the aforementioned organic resin particles,

[0318] The aforementioned EA and the aforementioned EB are in units of MPa. [5]

[0320] The coated metal sheet according to any one of [1] to [4], wherein

[0321] The aforementioned organic resin particles are resin particles made of a polyurethane-based resin,

[0322] The aforementioned polyurethane-based resin has a glass transition temperature Tg in the range of -40 to 40°C. [6]

[0324] The coated metal sheet according to any one of [1] to [4], wherein

[0325] The aforementioned organic resin particles are resin particles made of an acrylic resin,

[0326] The aforementioned acrylic resin has a glass transition temperature Tg in the range of 40 to 160°C. [7]

[0328] The coated metal sheet according to [6], wherein, in a cross section obtained by cutting the aforementioned organic resin coating layer at an arbitrary position in the thickness direction, a cross-sectional shape of at least a portion of the aforementioned resin particles made of an acrylic resin is a substantially elliptical shape,

[0329] The aforementioned substantially elliptical shape has a short axis direction that is substantially parallel to the thickness direction of the aforementioned organic resin coating layer, and a long axis direction that is substantially parallel to a direction orthogonal to the aforementioned thickness direction,

[0330] The aforementioned substantially elliptical shape has a short axis direction that is substantially parallel to the thickness direction of the aforementioned organic resin coating layer, and a long axis direction that is substantially parallel to a direction orthogonal to the aforementioned thickness direction,

[0331] 1.5 ≤ Mφ / T ≤ 80.0 … Equation (11)

[0332] Here, the aforementioned average length Mφ of the short axis is in units of μm. [8]

[0334] The coated metal sheet according to any one of [1] to [7], wherein the aforementioned metal sheet is a zinc-based plated steel sheet in which a zinc-based plating layer containing at least zinc is present on the surface of a base steel sheet. [9]

[0336] The coated metal sheet according to [8], wherein further, a rust-preventive coating layer containing a rust-preventive pigment and a resin is positioned between the aforementioned organic resin coating layer and the aforementioned zinc-based plating layer.

[10]

[0338] The coated metal sheet according to [9], wherein the aforementioned rust-preventive pigment is a pigment containing at least one or more of the elements P, V, Si, and Mg.

[11]

[0340] The coated metal sheet according to any one of [1] to

[10] , wherein the aforementioned organic resin coating layer further contains a colorant.

[0341] Textual translation in the drawings

[0342] 1 Coated metal sheet

[0343] 10 Metal sheet

[0344] 20, 25 Organic resin coating layer

[0345] 30 Rust-preventive coating layer

[0346] 201 Organic resin particles

[0347] 203 Binder resin

Claims

1. A coated metal sheet having: a metal sheet; an organic resin coating layer on a surface of the metal sheet; and organic resin particles dispersed in the organic resin coating layer, the content of the organic resin particles in the organic resin coating layer is 1.0 to 16.6% by volume per one side with respect to the total solid content volume of the organic resin coating layer, when the organic resin coating layer is viewed from above, the organic resin particles are dispersed in the organic resin coating layer at a surface density of 30 to 120 pieces / mm 2 , in a cross section obtained by cutting the organic resin coating layer in an arbitrary position in the thickness direction, the following relationships of Formulas (1) to (4) are satisfied, 10 < T < 40... Formula (1) 50 < φ < 100... Formula (2) 1.50 ≤ φ / T ≤ 10.00 … Equation (3) 15.00 ≤ φ / t ≤ 90.00 … Equation (4) In the Equations (1) to (4) above, T: average film thickness of the organic resin coating film layer in a portion where the organic resin particles are not present in the cross section, φ: average particle diameter of the organic resin particles, t: average film thickness of a portion where a site of the organic resin particle protruding from a position of a surface of the organic resin coating film layer in the cross section is covered with the organic resin coating film layer, that is, average film thickness of a particle covered portion, The T, the φ, and the t are in units of μm.

2. The coated metal plate according to claim 1, wherein The organic resin coating film layer is present on both surfaces of the metal sheet, and the organic resin particles are present only in the organic resin coating film layer present on one surface of the metal sheet, With respect to the two organic resin coating film layers present on both surfaces of the metal sheet, the following relationships shown in Equations (5) and (6) are satisfied, 3 ≤ GA ≤ 30 … Equation (5) 0.7 ≤ GA / GB ≤ 1.3 … Equation (6) In the Equations (5) and (6) above, GA: 60-degree specular glossiness G of the surface of the organic resin coating layer containing the organic resin particles, as defined in JIS Z 8741 : 1997 S (60°), GB: 60-degree specular glossiness G of the surface of the organic resin coating layer not containing the organic resin particles, prescribed in JIS Z 8741 : 1997 S (60°).

3. The coated metal sheet according to claim 1 or 2, wherein The T and the t satisfy the following relationship shown in Equation (7), 5.0 ≤ T / t ≤ 60.0 … Equation (7).

4. The coated metal sheet according to claim 1 or 2, wherein The binder resin contained in the organic resin coating film layer and the organic resin particles satisfy the following relationships shown in Equations (8) to (10), EA ≤ EB … Equation (8) 60 ≤ EA ≤ 150 … Equation (9) 60 ≤ EB ≤ 250 … Equation (10) In the Equations (8) to (10) above, EA: compressive elastic modulus at 25°C of the binder resin contained in the organic resin coating film layer, EB: compressive elastic modulus at 25°C of the organic resin particles, The EA and the EB are in units of MPa.

5. The coated metal sheet according to claim 1 or 2, wherein The organic resin particles are resin particles made of a polyurethane-based resin, The polyurethane-based resin has a glass transition temperature Tg in the range of -40 to 40°C.

6. The coated metal sheet according to claim 1 or 2, wherein The organic resin particles are resin particles made of an acrylic-based resin, The acrylic-based resin has a glass transition temperature Tg in the range of 40 to 160°C.

7. The coated metal plate according to claim 6, wherein In a cross section obtained by cutting the organic resin coating film layer at an arbitrary position in the thickness direction, a cross-sectional shape of at least a portion of the resin particles made of the acrylic-based resin is a substantially elliptical shape, A short axis direction of the substantially elliptical shape is substantially parallel to a thickness direction of the organic resin coating film layer, and a long axis direction of the substantially elliptical shape is substantially parallel to a direction orthogonal to the thickness direction, An average length Mφ of the short axis of the substantially elliptical shape and the T satisfy the following relationship shown in Equation (11), 1.5 ≤ Mφ / T ≤ 80.0 … Equation (11) Here, the average length Mφ of the short axis is in units of μm.

8. The coated metal sheet according to claim 1 or 2, wherein The metal sheet is a zinc-based plated steel sheet in which a zinc-based plating layer containing at least zinc is provided on the surface of a base steel sheet.

9. The coated metal sheet according to claim 8, wherein Further, a rust-preventive coating layer containing a rust-preventive pigment and a resin is provided between the organic resin coating layer and the zinc-based plating layer.

10. The coated metal sheet according to claim 9, wherein The rust-preventive pigment is a pigment containing at least one or more of the elements P, V, Si, and Mg.

11. The coated metal sheet according to claim 1 or 2, wherein The organic resin coating layer further contains a colorant.

Citation Information

Patent Citations

  • Organic-coated galvanized steel sheet and process for producing same

    WO2014112544A1